Alkaline‐Earth Metal Mediated Benzene‐to‐Biphenyl Coupling. (14th December 2022) - Mai, Jonathan; Morasch, Michael; Jędrzkiewicz, Dawid; Langer, Jens; Rösch, Bastian; Harder, Sjoerd
Abstract: Complex [( DIPeP BDI)Ca]2 (C6 H6 ), with a C6 H6 2− dianion bridging two Ca 2+ ions, reacts with benzene to yield [( DIPeP BDI)Ca]2 (biphenyl) with a bridging biphenyl 2− dianion ( DIPeP BDI=HC[C(Me)N‐DIPeP]2 ; DIPeP=2, 6‐CH(Et)2 ‐phenyl). The biphenyl complex was also prepared by reacting [( DIPeP BDI)Ca]2 (C6 H6 ) with biphenyl or by reduction of [( DIPeP BDI)CaI]2 with KC8 in presence of biphenyl. Benzene‐benzene coupling was also observed when the deep purple product of ball‐milling [( DIPP BDI)CaI(THF)]2 with K/KI was extracted with benzene (DIPP=2, 6‐CH(Me)2 ‐phenyl) giving crystalline [( DIPP BDI)Ca(THF)]2 (biphenyl) (52 % yield). Reduction of [( DIPeP BDI)SrI]2 with KC8 gave highly labile [( DIPeP BDI)Sr]2 (C6 H6 ) as a black powder (61 % yield) which reacts rapidly and selectively with benzene to [( DIPeP BDI)Sr]2 (biphenyl). DFT calculations show that the most likely route for biphenyl formation is a pathway in which the C6 H6 2− dianion attacks neutral benzene. This is facilitated by metal‐benzene coordination. Abstract : Attempts to isolate low‐valent (BDI)Ae‐Ae(BDI) complexes led to reduction of the benzene solvent and formation of (BDI)Ae‐(C6 H6 )‐Ae(BDI); BDI=β‐diketiminate ligand, Ae=Ca or Sr. Reaction of bridging C6 H6 2− with benzene gave (biphenyl) 2− complexes. Ball‐milling is an efficient synthetic tool for this dehydrogenative benzene‐benzene coupling. Calculations suggest attack of C6 H6 2− at benzene. This is facilitated by Ae 2+ ⋅⋅⋅benzene coordination.